2020
DOI: 10.1371/journal.pone.0243789
|View full text |Cite
|
Sign up to set email alerts
|

In-depth characterization and comparison of the N-glycosylated proteome of two-dimensional- and three-dimensional-cultured breast cancer cells and xenografted tumors

Abstract: Native intact N-glycopeptide analysis can provide access to the comprehensive characteristics of N-glycan occupancy, including N-glycosites, N-glycan compositions, and N-glycoproteins for complex samples. The sample pre-processing method used for the analysis of intact N-glycopeptides usually depends on the enrichment of low abundance N-glycopeptides from a tryptic peptide mixture using hydrophilic substances before LC-MS/MS detection. However, the number of identified intact N-glycopeptides remains inadequate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…David and coworkers reported that 3D cultures of ovarian cancer cell lines showed a higher resemblance in terms of mucin and truncated O-glycan footprint to tumour tissue than the same cell lines cultured as 2D cultures [ 96 ]. Other reports followed in gastric and breast cancer [ 97 , 98 ]. For the latter, the authors describe different N-glycosylation patterns for the same BC cells, when cultured in 2D, 3D and as mouse xenografts [ 98 ].…”
Section: Glycan-lectin Interactions: Novel Targets For Tumour-assomentioning
confidence: 99%
See 1 more Smart Citation
“…David and coworkers reported that 3D cultures of ovarian cancer cell lines showed a higher resemblance in terms of mucin and truncated O-glycan footprint to tumour tissue than the same cell lines cultured as 2D cultures [ 96 ]. Other reports followed in gastric and breast cancer [ 97 , 98 ]. For the latter, the authors describe different N-glycosylation patterns for the same BC cells, when cultured in 2D, 3D and as mouse xenografts [ 98 ].…”
Section: Glycan-lectin Interactions: Novel Targets For Tumour-assomentioning
confidence: 99%
“…Other reports followed in gastric and breast cancer [ 97 , 98 ]. For the latter, the authors describe different N-glycosylation patterns for the same BC cells, when cultured in 2D, 3D and as mouse xenografts [ 98 ].…”
Section: Glycan-lectin Interactions: Novel Targets For Tumour-assomentioning
confidence: 99%
“…Studies have shown that cells involved in a tumoroid perform metabolic and physical activities similar to what they do in native tissue. The ECM proteins produced by cells during tumoroid formation bind each other and form the complex networks that represent the tumor complexity as seen in xenografted tumors [ 117 , 118 ]. The methodologies to generate tumoroids are beyond the scope of this paper.…”
Section: Tumoroid Transformation To a Tumor By Host Fibroblasts Following Implantationmentioning
confidence: 99%
“…Glycosylation, a template‐free enzymatic process, is one of the most common protein post‐translational modifications in human cell lines 1 . At the same time, glycopeptides carry a wealth of personal biological information, and play a key role in various fundamental biological processes such as immune regulation, cell growth, cell–cell interaction and cell adhesion 2–4 .…”
Section: Introductionmentioning
confidence: 99%
“…Glycosylation, a template-free enzymatic process, is one of the most common protein post-translational modifications in human cell lines. 1 At the same time, glycopeptides carry a wealth of personal biological information, and play a key role in various fundamental biological processes such as immune regulation, cell growth, cell-cell interaction and cell adhesion. [2][3][4] Abnormal glycosylation is closely related to the progress of many tumor-related diseases; for instance, glycosylation disorders exist in the development and progression of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%